Crystallography at non-ambient conditions and physical properties of the synthesized double perovskites, Sr2(Co1−xFex)TeO6. Issue 13 (7th March 2023) - Zaraq, Asmaa; Orayech, Brahim; Igartua, Josu M.; El Bouari, Abdeslam; Gregory, Duncan H.; Gesing, Thorsten M.
Abstract : We report the synthesis of double perovskite oxides Sr2 (Co1− x Fe x )TeO6 obtained by solid-state reaction. The changes in the crystal structures of the samples due to iron substitution were studied using XRD, Raman spectroscopy and  57 Fe Mössbauer spectroscopy. Abstract : Polycrystalline double perovskite-type Sr2 (Co1− x Fe x )TeO6 with various stoichiometric compositions ( x = 0, 0.25, 0.5, 0.75, and 1) were synthesized by solid-state reactions in air. The crystal structures and phase transitions of this series at different temperature intervals were determined by X-ray powder diffraction, and from the obtained data the crystal structures were refined. It has been proven that for the compositions x = 0.25, 0.50, and 0.75, the phases crystallize at room temperature in the monoclinic space group I 2/ m . Down to 100 K, depending on the composition, these structures experience a phase transition from I 2/ m to P 21 / n . At high temperatures up to 1100 K their crystal structures show two further phase transitions. The first one is a first-order phase transition, from monoclinic I 2/ m to tetragonal I 4/ m, followed by a second-order phase transition to cubic Fm 3̄ m . Therefore, the phase transition sequence of this series detected at temperatures ranging from 100 K to 1100 K is P 21 / n → I 2/ m → I 4/ m → Fm 3̄ m . The temperature-dependent vibrational features of the octahedral sites were investigated by Raman spectroscopy, which furthermore complements the XRD results. A decrease in the phase-transition temperature with increasing iron content has been observed for these compounds. This fact is explained by the progressive diminishing of the distortion of the double-perovskite structure in this series. Using room-temperature Mössbauer spectroscopy, the presence of two iron sites is confirmed. The two different transition metal cations Co and Fe at the B sites allow exploring their effect on the optical band-gap.